2015
DOI: 10.1177/1687814014568499
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on heat transfer of a rotor blade tip with various film cooling holes arrangements and groove depths

Abstract: In this article, the effects of film cooling holes arrangement and groove depth on the heat transfer and film cooling performance of blade tip are investigated. For this numerical research, a high-pressure turbine blade with the squealer tip is applied, and the tip clearance is given to be 0.8 mm (1% of the blade span). Simultaneously, a typical tip cooling technology of film holes in the groove floor is used. The number of film holes is fixed at 10, and two kinds of holes arrangements are considered: (1) equi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 44 publications
(37 reference statements)
0
8
0
Order By: Relevance
“…Wang et al 10 concluded that increasing squealer width can reduce the velocity of leakage flow and the size of separation vortex, then reduce overall heat transfer processes. The research work of Tong et al 11 also showed that tip averaged HTC decreased with the increase of the squealer height. Bunker et al 12 tested and analyzed the influence of the squealer height on tip heat transfer processes.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…Wang et al 10 concluded that increasing squealer width can reduce the velocity of leakage flow and the size of separation vortex, then reduce overall heat transfer processes. The research work of Tong et al 11 also showed that tip averaged HTC decreased with the increase of the squealer height. Bunker et al 12 tested and analyzed the influence of the squealer height on tip heat transfer processes.…”
Section: Introductionmentioning
confidence: 86%
“…The research work of Tong et al. 11 also showed that tip averaged HTC decreased with the increase of the squealer height. Bunker et al.…”
Section: Introductionmentioning
confidence: 86%
“…They found that the cavity squealer tip can weaken the TLV effectively, and the mutation of mass-averaged aerodynamic loss of the cavity squealer tip is smaller than that of the plane tip with the increment of height-to-chord ratio. Tong et al (2015Tong et al ( , 2018 and Gao et al (2017) also concluded that the groove depth of squealer tip can influence the TLF. The optimum value of groove depth is about 2.5 percent of the blade span, and the larger or smaller value is not good for the blade tip flow.…”
Section: Introductionmentioning
confidence: 97%
“…They found that the cavity squealer tip can weaken the TLV effectively, and the mutation of mass-averaged aerodynamic loss of the cavity squealer tip is smaller than that of the plane tip with the increment of height-to-chord ratio. Tong et al . (2015, 2018) and Gao et al .…”
Section: Introductionmentioning
confidence: 99%
“…Film cooling is typically applied to turbine engines, 1 where cooling air is exhausted through small holes drilled into the blade, 2,3 which can have a higher turbine inlet temperature to improve the turbine performance. Moreover, in rocket engines, 4 film cooling can be used alone or in combination with regenerative cooling to protect the thruster wall.…”
Section: Introductionmentioning
confidence: 99%